2008
DOI: 10.1515/ijamh.2008.20.4.501
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, health, body mass index, sleeping habits and body complaints in Australian senior high school students

Abstract: Underweight, physical activity and good sleep are factors with significant positive effect on good health, whereas overweight is a negative factor. Proper sleep habits and higher physical activity levels should be promoted among high school students, and TV viewing time and video game use restricted. Additionally, schools should provide opportunities for young people to participate in a wider range of physical activities that address their individual needs while promoting the health benefits of engaging in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 27 publications
7
34
2
1
Order By: Relevance
“…Data from a large cross-sectional study of teenage females also found that PTSD diagnosis in adolescence was associated with poorer health outcomes, particularly more chronic conditions and reproductive health problems 9 . In our study, physical inactivity was significantly associated with health complaints, corroborating other studies, indicating a positive effect of physical activity on general health status 4,5,11,25,26 . The majority of studies investigated the role of physical activity in the relationship between school-related stress and adolescent health complaints 27,28 .…”
Section: Discussionsupporting
confidence: 92%
“…Data from a large cross-sectional study of teenage females also found that PTSD diagnosis in adolescence was associated with poorer health outcomes, particularly more chronic conditions and reproductive health problems 9 . In our study, physical inactivity was significantly associated with health complaints, corroborating other studies, indicating a positive effect of physical activity on general health status 4,5,11,25,26 . The majority of studies investigated the role of physical activity in the relationship between school-related stress and adolescent health complaints 27,28 .…”
Section: Discussionsupporting
confidence: 92%
“…The main finding in terms of musculoskeletal complaints was that pain was common among high school students, which is in accordance with previous studies (14,15,16,17,18). However, no differences were found between students with foreign and Swedish background.…”
Section: Musciiloskeletal Complaintssupporting
confidence: 91%
“…This survey was conducted among high school students based on a Swedish questionnaire previously published on groups of high school students from Sweden, Norway, and Australia (14)(15)(16)(17)(18). A test-retest of the questionnaire revealed a very good reliability (r= 1.0); no significant differences were found between test occasions (p = 1.0) (14).…”
Section: Questionnairementioning
confidence: 99%
“…One study that included a sample size of 9 adolescents within the age range was excluded 85 . A further 5 studies were considered eligible following a search of additional citations associated with the final included studies in Google Scholar, 37,86–89 resulting in a total of 20 studies included in the review. A PRISMA flow diagram outlining the screening and selection process is detailed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%